Intravenous methylprednisolone as a transition treatment in red ear syndrome: A case report - KOKAR, SERDAR (My University, 2023)
Red ear syndrome (RES) is a rare condition of unknown etiology characterized by episodic attacks of unilateral ear pain, redness, and burning sensation. A 31-year-old male patient was admitted to our clinic with a severe headache reaching up to 5 h, presenting with short bursts of electric shock-like sensation, burning, and tingling in the left side of his face. The patient was unresponsive to previous medical treatments. Lidocaine 10% through the intranasal route for sphenopalatine ganglion and stellate ganglion blockade under the guidance of fluoroscopy also failed. Given that the Red-Ear syndrome shares similar pathophysiological pathways with trigeminal autonomic cephalalgias, the patient was treated with high-dose intravenous methylprednisolone, and since then, he has been symptom-free for 6 months. High-dose steroid therapy might be a good alternative in late-onset RES as a transition treatment.

Kırmızı kulak sendromu; epizodik tek taraflı kulak ağrısı, kızarıklık ve yanma hissi ile karakterize, etyolojisi tam olarak bilinmeyen nadir bir bozukluktur. Otuz bir yaşındaki erkek hasta sol yüz yarımında yanma, karıncalanma ve elektrik çarpması şeklinde ortaya çıkan ve beş saate kadar uzayabilen baş ağrısı şikayeti ile kliniğimize başvurdu. Önceki medikal tedavilere yanıt vermemiş olan hastaya intranazal yolla lidokain %10 ve floroskopi rehberliğinde stellat ganglion blokajı tedavileri sırasıyla uygulandı. Hasta bahsi geçen girişimsel ağrı tedavilerine de yanıt vermedi. Kırmızı kulak sendromunun trigeminal otonomik sefaljilerle benzer patofizyolojik özellikleri paylaştığı görüşünden yola çıkarak, hasta yüksek doz intravenöz metilprednizolon ile tedavi edildi ve takip eden altı ay süresince ağrısız olarak izlendi. Geç başlangıçlı kırmızı kulak sendromunun geçiş tedavisinde, yüksek doz steroidler iyi birer alternatif olarak değerlendirilebilir.
Kırmızı kulak sendromunun geçiş tedavisinde intravenöz metilprednizolon: Bir olgu sunumu
Keywords: Tıp; Cerrahi Tıp Bilimleri; Anesteziyoloji; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Anesthesiology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ANESTEZİYOLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; ANESTHESIOLOGY; Anesteziyoloji ve Ağrı Tıbbı; Anesthesiology and Pain Medicine; Facial pain; headache disorders; sphenopalatine ganglion; stellate ganglion; steroid; Baş ağrısı; yüz ağrısı